2005
DOI: 10.1007/s11104-004-0271-y
|View full text |Cite
|
Sign up to set email alerts
|

Crop row spacing and its influence on the partitioning of evapotranspiration by winter-grown wheat in Northern Syria

Abstract: A study was conducted during the 1996-97 crop growth season at ICARDA in northern Syria, to investigate the influence of wheat canopy architecture on the partitioning of moisture between soil evaporation and crop transpiration, on a soil with high hydraulic conductivity. The study was conducted on the long-term two course wheat-lentil rotation trial, established on a swelling clay soil (Calcixerollic xerochrept). The wheat canopy architecture was manipulated by sowing the crop at either of two row-spacings, 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
50
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(55 citation statements)
references
References 28 publications
3
50
0
2
Order By: Relevance
“…Some researchers studied the effects of deficit irrigation on the evapotranspiration (Eberbach and Pala 2005), water use efficiency (Lauenroth et al 2000, Angus and Van Herwaarden 2001, Li et al 2008b) and yield (Pan et al 2003) of winter wheat; Zhang et al (1999) discussed the relationship between evapotranspiration and yield. These studies, however, have not reported the integrated effects of the deficit irrigation on the radiation use efficiency (RUE) in North China.…”
mentioning
confidence: 99%
“…Some researchers studied the effects of deficit irrigation on the evapotranspiration (Eberbach and Pala 2005), water use efficiency (Lauenroth et al 2000, Angus and Van Herwaarden 2001, Li et al 2008b) and yield (Pan et al 2003) of winter wheat; Zhang et al (1999) discussed the relationship between evapotranspiration and yield. These studies, however, have not reported the integrated effects of the deficit irrigation on the radiation use efficiency (RUE) in North China.…”
mentioning
confidence: 99%
“…В исследованиях применялись полевой, вегетационный и лабораторный методы (Foulkes et al, 2011;Hochman et al, 2009;Naresh et al, 2012;Oyewole, Attah, 2007); свойства почв определялись по общепринятым методикам (Eberbach, Pala, 2005;Foulkes et al, 2011;Malik et al, 2009). Оценка качества посева проводилась в полупроизводственных опытах по основным предшественникам яровой пшеницы (пар, горох, пшеница) в трехкратной повторности по схеме, представленной в табл.…”
Section: материалы и методы исследованийunclassified
“…Среди агротехнических приемов (предшественник, обработка почвы и др.) в получении полноценных всходов зерновых немаловажное значение имеет посев (Chen et al, 2010;Eberbach, Pala, 2005;Foulkes et al, 2011;Naresh et al, 2012). Задача посева состоит в получении дружных всходов посредством оптимального использования способа, срока посева, нормы высева, глубины заделки и распределении семян, ширины междурядий (Chen et al, 2010;Liang et al, 2011;Pandey et al, 2013;Shah et al, 2006).…”
Section: результаты и обсуждениеunclassified
“…Row spacing requirements of wheat depend on architecture and growth pattern of the varieties. For higher yield, higher proportion of incident radiation at the soil surface must be intercepted by the crop canopy (Eberbach and Pala, 2005). Skip planting geometry with pairs of row allow more light penetration inside plant canopy, while in solid geometry the field is more populated and there is less light penetration inside plant canopy.…”
Section: International Journal Of Current Microbiology and Applied Scmentioning
confidence: 99%